Theoretical and Experimental Comparison Results of Dual-Channel 3D Quasi-Optical Network System between Frequency Selective Surface and Wire Grid Polarizer - Hai Wang; Xiaoming Liu; Junsheng Yu; Zejian Lu; Xiaodong Chen (International Journal of Antennas and Propagation)
A dual-channel 3D quasi-optical network (QON) system is analyzed and compared by theoretical and experimental results. It is divided into dual-channel signals by frequency selective surface (FSS) or wire grid polarizer (WGP) for transmitting the 324 GHz signal on the top layer while diverting the 183 GHz signal to the bottom layer. The system structure based on the beam radius is traced by the complex beam parameter and system transfer matrix for deciding the positions of cascade mirrors. The design principles and test results of FSS with perforated hexagonal array and WGP printed on the dielectric substrate are discussed together. In order to evaluate channel performance, the output planar near-fields of QON system are simulated and tested by the four reflections and three transmission results, respectively, where both scalar and vector conversion efficiencies are used to evaluate the quality of output beams. For the distortion phenomenon and energy loss in planar field, the aperture modes of corrugated horn feeds are analyzed by spherical wave expansion (SWE) to explain the asymmetrical pattern characteristic. The cut section of the far-field pattern is also directly measured in the compact antenna test range (CATR), comparing with the far-field patterns that are indirectly obtained based on the principle of near-to-far-field transformation and ideal aperture field integral of quiet zone (QZ). The differences between the near- and far-field test in QON have been compared, and discussion that the corresponding experimental results verify the WGP has better work performance in the good pattern symmetry, high cross-polarization isolation, low energy loss, and side-lobe level.